CYP2C19 loss-of-function alleles are not associated with clinical outcome of clopidogrel therapy in patients treated with newer-generation drug-eluting stents. Issue 26 (June 2016) - Choi, Ik Jun; Koh, Yoon-Seok; Park, Mahn-Won; Her, Sung Ho; Choi, Yun-Seok; Park, Chul-Soo; Park, Hun-Jun; Kim, Pum-Joon; Chung, Wook-Sung; Kim, Ho-Sook; Shin, Jae-Gook; Seung, Ki-Bae; et al.
Abstract : Abstract: CYP2C19 loss-of-function (LOF) alleles adversely affect clinical outcome of clopidogrel therapy. Recent introduction of a newer-generation drug-eluting stent (DES) has significantly reduced the occurrence of stent thrombosis. The aim of this study was to evaluate the impact of CYP2C19 LOF alleles on clinical outcome in patients treated with the newer-generation DES. The effects of CYP2C19 genotypes were evaluated on clinical outcome of clopidogrel therapy in 2062 patients treated with percutaneous coronary intervention using either first-generation DES (sirolimus- and paclitaxel-eluting stent, n = 1349) or newer-generation DES (everolimus- and zotarolimus-eluting stent, n = 713). The primary clinical outcome was major cardiac and cerebrovascular event (MACCE) including cardiac death, nonfatal myocardial infarction, stroke, and stent thrombosis during 1 year of follow-up. CYP2C19 LOF alleles were significantly associated with a higher risk of MACCE in patients treated with first-generation DES (hazard ratio [HR] 2.599, 95% confidence interval [CI] 1.047–6.453; P = 0.034). In contrast, CYP2C19 LOF alleles were not associated with primary outcome in newer-generation DES (HR 0.716, 95% CI 0.316–1.622; P = 0.522). In the further multivariate analysis, CYP2C19 LOF alleles were not associated with MACCE in patients receiving newer-generation DES (adjusted HR 0.540, 95% CI 0.226–1.291; P = 0.166), whereas they were demonstrated to be an independent risk factor for MACCE in those implanted with first-generation DES (adjusted HR 3.501, 95% CI 1.194–10.262; P = 0.022). In contradiction to their clinical impact in first-generation DES era, CYP2C19 LOF alleles may not affect clinical outcome of clopidogrel therapy in patients treated with newer-generation DES.